The Negative Elevation‐Dependent Pattern of Non‐Growing Season CO2 Loss From Alpine Frozen Ground - Zhaoheng Deng; Jiabin Fan; Da Wei; Yahui Qi; Jing Tao; Zhuangzhuang Wang; Liqin Hua; Xiaodan Wang (Geophysical Research Letters)
Abstract Substantial organic carbon stores in the soil of high‐elevation regions are vulnerable to rapid warming. The “Third Pole”, encompassing the Tibetan Plateau and adjacent regions, is home to the largest alpine permafrost on the Earth. Through analysis of 118 eddy covariance and chamber observations in the non‐growing season—a unique time window for examining soil CO2 loss, we report a negative elevation‐dependent pattern. More importantly, there is a negative elevation‐dependent pattern regarding the temperature sensitivities of CO2 loss, determined by the soil carbon content. We project that, compared to low elevations, future increases in CO2 loss will be lower at high elevations (>4,000 m) with lower soil organic carbon. The pattern of alpine soil CO2 loss, in which the higher the elevation and the colder it is, the less sensitive the loss is to warming, implies limited CO2 will be lost in the future from high‐elevation permafrost regions.